INFLUENCE OF COMBINED ANTIHYPERTENSIVE AND ANTIDEPRESSANT THERAPY ON LEFT VENTRICULAR REMODELING IN PATIENTS WITH ARTERIAL HYPERTENSION, ANXIETY AND DEPRESSION - Y. A. Vasyuk; T. V. Dovzenko; E. A. Nesterova; I. A. Sadulaeva; K. V. Tarasova (Рациональная фармакотерапия в кардиологии)
Aim. To assess influence of combined antihypertensive (captopril or metoprolol) and antidepressant (thianeptin or sertralin) therapy on clinical status, blood pressure (BP) and myocardial function in patients with arterial hypertension (HT) and affective disorders (AD).Material and methods. 106 patients with HT were involved in the study. 64 patients (60,4%) had concomitant AD. All patients were divided into 3 groups. 46 patients with HT and AD were included in the 1-st group. They received metoprolol or captopril in combination with tianeptine or sertaline. The 2-nd group included 18 patients with HT and AD who received only antihypertensive therapy. The 3-rd group consisted of 42 patients with HT without AD. They also received only antihypertensive therapy.Results. After 6 month therapy patients of the 1-st and the 3-rd groups had more significant clinical improvement and BP reduction (according to 24- hour BP monitoring) as well as more farourable structural and functional changes of left ventricular in comparison with patients of the 2-nd group.Conclusion. In patients with HT and concomitant AD combined antihypertensive and antidepressant therapy result in favourable clinical changes, effectively reduce BP, improve left ventricular structure and function.